Mixed Cations Enabled Combined Bulk and Interfacial Passivation for Efficient and Stable Perovskite Solar Cells - Wu, Pengfei; Wang, Shirong; Heo, Jin Hyuck; Liu, Hongli; Chen, Xihan; Li, Xianggao; Zhang, Fei (Nano-Micro Letters, 2023)
Here, we report a mixed GAI and MAI (MGM) treatment method by forming a 2D alternating-cation-interlayer (ACI) phase (n = 2) perovskite layer on the 3D perovskite, modulating the bulk and interfacial defects in the perovskite films simultaneously, leading to the suppressed nonradiative recombination, longer lifetime, higher mobility, and reduced trap density. Consequently, the devices’ performance is enhanced to 24.5% and 18.7% for 0.12 and 64 cm2, respectively. In addition, the MGM treatment can be applied to a wide range of perovskite compositions, including MA-, FA-, MAFA-, and CsFAMA-based lead halide perovskites, making it a general method for preparing efficient perovskite solar cells. Without encapsulation, the treated devices show improved stabilities. Highlights: 1 A mixed GAI and MAI (MGM) treatment modulating the bulk and interfacial defects simultaneously is reported. 2 The devices’ performance is enhanced to ~24.5% in 0.12 cm2 and ~18.7% in 64 cm2 with improved stability. 3 The MGM treatment can be applied to a wide range of perovskite compositions.